1974
DOI: 10.2307/1935459
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Effort in Anoline Lizards

Abstract: Lizards in the large neotropical genus Anolis exhibit an unusual mode of reproduction; all species lay a clutch of a single egg. In contrast, the more typical pattern for lizards is a multi—egg clutch in which the number of eggs increases with female size both inter— and intra—specifically. In Anolis low clutch number is associated with a potential for frequent ovipositions. Field rates for several tropical forest species are one egg every 1—2 wk. Thus, high rates of egg production coupled with a generation ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
130
1
3

Year Published

1976
1976
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(141 citation statements)
references
References 37 publications
7
130
1
3
Order By: Relevance
“…Aquino, unpubl. data), Leposoma scincoides (TEIXEIRA & FONSECA 2003), Cercosaura eigenmannii (Griffin, 1917) (VITT et al 1998), Alopoglossus angulatus (Linnaeus, 1758) and A. atriventis (TINKLE et al 1970), leading females to produce clutches in a fast, consecutive, and continuous fashion (ANDREWS & RAND 1974, VITT 1986, DOUGHTY 1997, PIANKA & VITT 2003. Indeed, most reproduction of D. nordestina occurs from May to June (when most reproductive females and the only gravid ones were found), with most juveniles emerging subsequently from July through November.…”
Section: Discussionmentioning
confidence: 99%
“…Aquino, unpubl. data), Leposoma scincoides (TEIXEIRA & FONSECA 2003), Cercosaura eigenmannii (Griffin, 1917) (VITT et al 1998), Alopoglossus angulatus (Linnaeus, 1758) and A. atriventis (TINKLE et al 1970), leading females to produce clutches in a fast, consecutive, and continuous fashion (ANDREWS & RAND 1974, VITT 1986, DOUGHTY 1997, PIANKA & VITT 2003. Indeed, most reproduction of D. nordestina occurs from May to June (when most reproductive females and the only gravid ones were found), with most juveniles emerging subsequently from July through November.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative studies suggest that offspring size is correlated with adult life-history traits (Blueweiss et al, 1978;CluttonBrock and Harvey, 1979;Peters, 1983;Calder, 1984) in a variety of taxa, including mammals (Leutenegger, 1976(Leutenegger, , 1979Steams, 1983;Harvey and Clutton-Brock, 1985;Gittleman, 1986), reptiles (Andrews and Rand, 1974;Steams, 1984;Dunham and Miles, 1985), and amphibians (Kaplan and Salthe, 1979). These allometric relationships are thought to reflect underlying physiological and functional constraints on life histories and, as such, show taxon-specific relationships (Steams, 1980;Dunham et a1., 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Also, traits that help reduce the variability in reproductive output produced by a variable pattern of energy availability have not received much attention. Andrews and Rand (1974) suggested that flexibility in the timing of egg deposition was an important adaptation of Anolis lizards to unpredictable, short-term climatic fluctuations. This flexibility generally seems optimal to an individual when selection favors both increased longevity and high reproductive output, as was argued for B. attenuatus.…”
Section: Climate and Life-histories Of West Coast Plethodontid Salamamentioning
confidence: 99%